Pain assessment and management in patients undergoing endovascular procedures in the catheterization laboratory - Thamires de Souza Hilário; Simone Marques dos Santos; Juliana Kruger; Martha Georgina Goes; Márcia Flores Casco; Eneida Rejane Rabelo-Silva
Abstract OBJECTIVE To describe how pain is assessed (characteristic, location, and intensity) and managed in clinical practice in patients undergoing endovascular procedures in the catheterization laboratory setting. METHOD Cross-sectional study with retrospective data collection. RESULTS Overall, 345 patients were included; 116 (34%) experienced post-procedural pain; in 107 (92%), pain characteristics were not recorded; the location of pain was reported in 100% of patients, and its intensity in 111 (96%); management was largely pharmacologic; of the patients who received some type of management (n=71), 42 (59%) underwent reassessment of pain. CONCLUSION The location and intensity of pain are well reported in clinical practice. Pharmacologic pain management is still prevalent. Additional efforts are needed to ensure recording of the characteristics of pain and its reassessment after interventions.